2021
DOI: 10.1039/d0se01433h
|View full text |Cite
|
Sign up to set email alerts
|

Chicken feather fiber-based bio-piezoelectric energy harvester: an efficient green energy source for flexible electronics

Abstract: Large demands of wearable electronics and self-powered biomedical devices have triggered the search for efficient, biocompatible, flexible energy harvesters. However it is still challenging to develop such advanced energy harvesters...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Kar et al. [ 132 ] developed a flexible, biocompatible, and biodegradable energy harvester using chicken‐feather fibers. These fibers are an abundant biowaste material, with excellent mechanical characteristics and a high surface‐to‐weight ratio.…”
Section: E‐skins: Definitions and Mechanisms Of Transductionmentioning
confidence: 99%
“…Kar et al. [ 132 ] developed a flexible, biocompatible, and biodegradable energy harvester using chicken‐feather fibers. These fibers are an abundant biowaste material, with excellent mechanical characteristics and a high surface‐to‐weight ratio.…”
Section: E‐skins: Definitions and Mechanisms Of Transductionmentioning
confidence: 99%
“…Green energy harvesting techniques from the ambient environment are categorized based on natural energy sources such as solar, thermal, electromechanical, and mechanical 1‐5 . Among the different conversion methods piezoelectric nanogenerator (NG) is a powerful and upcoming approach for converting low‐frequency mechanical energy into electricity that works through the piezoelectric potential created by an externally applied strain in a piezoelectric material for driving the flow of electrons to the external load 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Green energy harvesting techniques from the ambient environment are categorized based on natural energy sources such as solar, thermal, electromechanical, and mechanical. [1][2][3][4][5] Among the different conversion methods piezoelectric nanogenerator (NG) is a powerful and upcoming approach for converting low-frequency mechanical energy into electricity that works through the piezoelectric potential created by an externally applied strain in a piezoelectric material for driving the flow of electrons to the external load. 6,7 Recently human-motionbased piezoelectric energy harvesters (PZEH) have attracted tremendous interest due to their potential applications in portable, embedded, and wearable smart electronics that require a self-sufficient and sustainable power source.…”
Section: Introductionmentioning
confidence: 99%
“…The chicken feather-based fiber has also been demonstrated as an energy harvester which could generate an approximate 10 V output voltage wherein the power density and current density have been recorded as 6 mW/cm 2 and 1.8 mA/cm 2 , respectively, under biomechanical pressure (0.13− 0.31 MPa) exerted by tapping. 27 Considering the upcoming requirement of natural materialbased energy harvesting technology, our present study has demonstrated on the development of a completely organicbased hybrid (piezo-cum-tribo) energy harvester using the casein/polyvinyl alcohol (PVA) blend material. In this study, casein/PVA in the form of a NF web has mainly been explored as a piezoelectric-cum-triboelectric component.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, activated carbon and a DNA-filled polymer have been studied as an energy harvester which has exhibited open-circuit voltages of 49.6 and 20 V. , Kumar et al have reported that fish scale particles in the PVDF matrix can show a voltage of 22 V and a high energy density of 28.5 μW/cm 2 . The chicken feather-based fiber has also been demonstrated as an energy harvester which could generate an approximate 10 V output voltage wherein the power density and current density have been recorded as 6 mW/cm 2 and 1.8 mA/cm 2 , respectively, under biomechanical pressure (0.13–0.31 MPa) exerted by tapping …”
Section: Introductionmentioning
confidence: 99%